2016
DOI: 10.2135/cropsci2015.08.0508
|View full text |Cite
|
Sign up to set email alerts
|

Sward Structure, Light Interception, and Rhizome‐Root Responses of Rhizoma Peanut Cultivars and Germplasm to Grazing Management

Abstract: ‘Florigraze’ rhizoma peanut (RP; Arachis glabrata Benth.) is a persistent forage legume for the US Gulf Coast, but peanut stunt virus (Cucumovirus spp.) reduces herbage accumulation (HA). Less susceptible germplasms and cultivars of RP have been released, but their responses to grazing management are not known. The objective was to quantify aboveground and belowground sward responses to grazing management of RP entries differing in growth habit to explain HA and persistence. Treatments were all combinations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 19 publications
(36 citation statements)
references
References 18 publications
(48 reference statements)
3
30
3
Order By: Relevance
“…Herbage bulk density in the current experiment is greater than reported previously for less intensively grazed Ecoturf (0.18-0.27 Mg dry matter ha −1 cm −1 ; Mullenix et al, 2016b). They did find, however, that Ecoturf pregrazing canopy height was shorter and herbage bulk density greater than those of Florigraze, Tito, and Peace across seasons and for RI of both 3 and 6 wk.…”
Section: Herbage Bulk Densitycontrasting
confidence: 79%
See 2 more Smart Citations
“…Herbage bulk density in the current experiment is greater than reported previously for less intensively grazed Ecoturf (0.18-0.27 Mg dry matter ha −1 cm −1 ; Mullenix et al, 2016b). They did find, however, that Ecoturf pregrazing canopy height was shorter and herbage bulk density greater than those of Florigraze, Tito, and Peace across seasons and for RI of both 3 and 6 wk.…”
Section: Herbage Bulk Densitycontrasting
confidence: 79%
“…These data are markedly different than those reported for closely and frequently grazed Florigraze RP, where root-rhizome mass decreased from 4.0 to ?0.5 Mg ha −1 during 2 yr of grazing (Ortega-S. et al, 1992b). A previous report showed that Ecoturf had greater root-rhizome mass than Florigraze under a range of grazing treatments (4450 and 3490 kg ha −1 , respectively; Mullenix et al, 2016b). Change for Ecoturf over a comparable timeframe in the current study was a 1.5-Mg ha −1 increase in rhizome mass for the 1-wk RI and no change for the 4-cm SH treatments.…”
Section: Root-rhizome Mass and Total Nonstructural Carbohydrate Poolsupporting
confidence: 58%
See 1 more Smart Citation
“…Although efforts continue to increase adoption of legumes in warm-climate grasslands (Castillo et al, 2014;Mullenix et al, 2016aMullenix et al, , 2016b, the effect of legume proportion on grass sward nutrient cycling is not well understood, particularly when compared with grass monocultures receiving N fertilizer. The objective of this study was to quantify the effects of N fertilization of bahiagrass monoculture and the proportion of rhizoma peanut (Arachis glabrata Benth.)…”
mentioning
confidence: 99%
“…Leaf samples were reweighted after the burn trial and divided by their pre‐trail mass to determine the ratio of leaf mass consumed (g/g). Nonstructural carbohydrate concentrations were measured in under‐ground storage organs and fibrous roots of three individuals of each species using the method of Mullenix et al () and expressed as concentrations (mg/g; Diaz‐Toribio, ).…”
Section: Methodsmentioning
confidence: 99%